2019
DOI: 10.26464/epp2019050
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal evolution of the effects of the El Niño–Southern Oscillation on lower stratospheric water vapor: Delayed effects in late winter and early spring

Abstract: Water vapor in the stratosphere makes a significant contribution to global climate change by altering the radiative energy budget of the Earth's climate system. Although many previous studies have shown that the El Niño–Southern Oscillation (ENSO) has significant effects on the water vapor content of the stratosphere in terms of the annual or seasonal mean, a comprehensive analysis of the seasonal evolution of these effects is still required. Using reanalysis data and satellite observations, we carried out a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…On the contrary, during moderate El Niño winters, dipole-shaped wet and dry regions of comparable intensity are observed in the Indo-Western Pacific and Central-Eastern Pacific, respectively. This is similar to the previously observed annual average distribution of 100 hPa water vapor in response to the El Niño signal [30,31,43], i.e., cooling in the tropical central-eastern Pacific at 100 hPa is accompanied by negative water vapor anomalies, while warming in the western Pacific corresponds to positive water vapor anomalies. However, unlike the distribution of annual mean water vapor anomalies, the wetness of the western Pacific is comparable to the dryness of the central-eastern Pacific during the winter of moderate El Niño; thus, the net impact of water vapor in the lower stratosphere tends to be zero after zonally averaged.…”
Section: Water Vapor Response To Extreme and Moderate El Niñosupporting
confidence: 90%
See 2 more Smart Citations
“…On the contrary, during moderate El Niño winters, dipole-shaped wet and dry regions of comparable intensity are observed in the Indo-Western Pacific and Central-Eastern Pacific, respectively. This is similar to the previously observed annual average distribution of 100 hPa water vapor in response to the El Niño signal [30,31,43], i.e., cooling in the tropical central-eastern Pacific at 100 hPa is accompanied by negative water vapor anomalies, while warming in the western Pacific corresponds to positive water vapor anomalies. However, unlike the distribution of annual mean water vapor anomalies, the wetness of the western Pacific is comparable to the dryness of the central-eastern Pacific during the winter of moderate El Niño; thus, the net impact of water vapor in the lower stratosphere tends to be zero after zonally averaged.…”
Section: Water Vapor Response To Extreme and Moderate El Niñosupporting
confidence: 90%
“…Furthermore, our previous study [43] proposed that the impact of ENSO on stratospheric water vapor is more pronounced in spring as a result of the lag in stratospheric response to ENSO signals. In this study, we found that only moderate El Niño events exhibit a lagged effect, while extreme events elicit a strong response in the stratosphere regardless of the season, which provides new insights for future research on extreme climate events.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…El Niño warms the cold point (Calvo et al, 2010;Free & Seidel, 2009;García-Herrera et al, 2006; W. J. Randel, Garcia, et al, 2009;Scaife et al, 2003) leading to an increase in SWV (Fueglistaler & Haynes, 2005;Garfinkel et al, 2013;Gettelman et al, 2001;Konopka et al, 2016;Liao et al, 2019;Lu et al, 2020;Randel et al, 2004;Scaife et al, 2003). Consistent with this, cold point temperatures (Figures 3b and 3c) and SWV (Figure 4a) both increase throughout the 10 year simulations.…”
Section: Stratospheric Water Vapormentioning
confidence: 55%
“…The concentration of water vapor in the stratosphere varies on both interannual and multi‐decadal timescales (W. J. Randel, Garcia, et al., 2009; W. J. Randel, Shine, et al., 2009; Solomon et al., 2010; Yu et al., 2022). El Niño warms the cold point (Calvo et al., 2010; Free & Seidel, 2009; García‐Herrera et al., 2006; W. J. Randel, Garcia, et al., 2009; Scaife et al., 2003) leading to an increase in SWV (Fueglistaler & Haynes, 2005; Garfinkel et al., 2013; Gettelman et al., 2001; Konopka et al., 2016; Liao et al., 2019; Lu et al., 2020; Randel et al., 2004; Scaife et al., 2003). Consistent with this, cold point temperatures (Figures 3b and 3c) and SWV (Figure 4a) both increase throughout the 10 year simulations.…”
Section: Stratospheric Water Vapormentioning
confidence: 99%